2018
DOI: 10.1039/c7ta11135e
|View full text |Cite
|
Sign up to set email alerts
|

Construction of microfluidic-oriented polyaniline nanorod arrays/graphene composite fibers for application in wearable micro-supercapacitors

Abstract: We demonstrated a new strategy to construct high-performance micro-SCs based on microfluidic-oriented core–sheath structured polyaniline nanorod arrays/graphene fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 45 publications
3
92
0
Order By: Relevance
“…The progress in the design of the spinneret is highlighted by introducing microfluidic spinnerets for complex component spinning, as it has rendered GBFs with desirable structures in a simple process . We have designed a microfluidic spinneret where GO and poly(vinyl alcohol) (PVA)/alginate sodium component could be extruded spontaneously from one outlet, forming a GO/PVA‐alginate/GO layered structure in a coagulation bath for shape fixing.…”
Section: Advance In Preparation Of Gbfsmentioning
confidence: 99%
“…The progress in the design of the spinneret is highlighted by introducing microfluidic spinnerets for complex component spinning, as it has rendered GBFs with desirable structures in a simple process . We have designed a microfluidic spinneret where GO and poly(vinyl alcohol) (PVA)/alginate sodium component could be extruded spontaneously from one outlet, forming a GO/PVA‐alginate/GO layered structure in a coagulation bath for shape fixing.…”
Section: Advance In Preparation Of Gbfsmentioning
confidence: 99%
“…Apart from the 2D materials discussed above, many 2D conducting polymers are also applicable for MSC electrode applications, including PANI, PPy, and polydopamine (PDA) . Generally speaking, 2D polymers have a variety of merits for electrochemical applications, but face problems of limited electrical conductivity.…”
Section: Planar Mesdsmentioning
confidence: 99%
“…Apart from the 2D materials discussed above,m any 2D conductingp olymers are also applicable for MSC electrode applications,i ncluding PANI, [36] PPy, [84] and polydopamine (PDA). [23] Generally speaking, 2D polymers have av ariety of merits for electrochemical applications,but face problems of limited electrical conductivity.A ne ffective strategy is to combine them with the materials that have high electrical conductivity.W u et al reported the fabrication of ah ybrid film of thiophene (TP) nanosheets and EG for MSCs( TP/EG MSCs).…”
Section: Sandwich-like Stacked Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other alternative strategies, regarding coating and impregnated reaction methods that could efficiently introduce electroactive materials in fibres enabled FFSCs to perform excellent energy storage ability. In this respect, the energy densities were promoted by electrochemically active materials (e.g., metal oxides/sulfides (Mno 2 , Co 3 O 4 , MoS 2 ) and conducting polymer (polyaniline, polypyrrole)) induced pseudo‐capacitances. Although those approaches have improved the energy densities of FFSCs, these levels are still relatively too low to meet the demands of practical application.…”
Section: Introductionmentioning
confidence: 99%